Assessing improvements in participants’ understanding of data through a DALI-based workshop - Oktavia, Rini; Yuni, Syarifah Meurah; Meutia, Ernita Dewi (Malaysian Journal of Library and Information Science, 2025)
As data increasingly influences decision-making in educational and professional settings, data literacy has become an essential competency. This study examines the effectiveness of a workshop conducted according to the Data Literacy (DALI) for Citizenship Framework, which comprises three main components: understanding data, acting on data, and engaging with data. This study focused solely on the data understanding component. The aim was to assess whether a DALI-based educational intervention could improve participants’ data literacy and learning experiences. Using a pre- and post-test design, data were collected from 35 participants in Aceh, Indonesia, who completed the workshop with a 10-item questionnaire to assess understanding of data types and a follow-up semi-structured interview to explore participants’ learning experiences. A paired t-test analysis revealed a significant increase in participants’ understanding of data types following the workshop; however, Cohen’s d effect size indicated a moderate effect. The follow-up interview showed that the workshop increased participants’ awareness of the importance of data literacy for decision-making. The workshop also enhanced participants’ understanding that, every day, they are acting on and engaging with data. Participants reported positive perceptions of their learning experience, suggesting that the workshop facilitated engagement, understanding, and confidence in working with data. These findings illustrate the significance of systematic, theory-based methodologies in data literacy education. The study provides empirical validation of the DALI framework as an evaluation and instructional instrument, offering evidence for its use in educational and professional development contexts and advancing research on effective data literacy pedagogy.